(untitled) (International Journal of Medical and Surgical Sciences, 2018)
Before the advent of anaesthesia in surgical practice, surgeons battled with patient’s maximal co-operation during surgical procedures, management of pain intra-operatively and post-operatively. Anaesthesia has greatly aided in overcoming these challenges, but a sizable proportion of reduction in these challenges but approximately 30-80% of patients complain of moderate to severe pain post-operatively indicating that post-operative pain remains a problem. Controlled epidural anaesthesia and controlled peripheral nerve block which are types of regional anaesthesia provide superior pain relief during and after surgery, making regional anaesthesia of particular relevance in orthopaedic surgery. More so, general anaesthesia has some adverse effects on the outcome of operation and the patient. These adverse effects are rare but may be disastrous and life-threatening necessitating close supervision during and after general anaesthesia. Hence, the preference should be towards regional anaesthesia with regards to the choice of anaesthesia in orthopaedic surgery. This review aims to highlight some concepts and techniques on regional anaesthesia in orthopaedic surgery.